ANALISIS PENGUKURAN DAN PERHITUNGAN DAYA LISTRIK DENGAN SISTEM MONITORING BERBASIS WEB DI AREA INDUSTRI - Kusuma, Dumung Weling; Triyanto, Aripin (Jurnal Teknik Elektro, 2024)
The use of electricity must be paid more attention so that there is no overrun of electricity costs. Because of these problems, the author took the title Analysis of electrical power measurement and calculation with web-based system monitoring in industrial areas. This study uses a calculation and measurement research methodology. After measurements and calculations are carried out with system monitoring, the results of the calculation of electrical power measurements and observations are obtained by analyzing the percentage of error values from the comparison of values obtained from the measurement results using the energy monitoring system with the value of the measurement results using the Power monitoring sensor (PMS) and calculations using formulas. The final result of this study was obtained from the results of monitoring voltage, current, power, and power factor. For the results of the analysis of the percentage of electrical power error values, it was carried out by comparing the calculation of Power Monitoring Sensor (PMS) with Energy Monitoring System (EMS) with a monitoring time of 3 months, the first month had an error value of 0.6%, the second month had an error value of 0.2%, and the second month had an error value of 0.1%. Thus, the difference in error values is quite small, it can be concluded that this tool is said to be quite good in monitoring the use of electrical power in industrial areas.